Analisis SWOT Implementasi Green Computing Di Sekolah Kejuruan ( Studi Kasus Pada SMK XYZ) - Dwi Remawati (STMIK Sinar Nusantara, 2014)
Many convenience obtained by using the computer as a tool or utilization of Information and Communication Technology (ICT), but there are also effects. ICT is actually not environmentally friendly because the amount of energy used to operate the ICT equipment, rising energy costs, as well as the waste generated by the ICT equipment that is not properly processed, also the lack of peduliannya humans on the environment and this makes the earth where human life is getting damaged due to poorly-maintained and it is certainly can be detrimental to mankind. The purpose of the application of green computing is to minimize energy consumption in IT, purchasing energy-efficient equipment, reducing the use of paper and other consumables, optimize data center efficiency, and reduce impact on the environment. This study to determine whether the strategy is appropriate terapkannya green computing. After the SWOT analysis has found that the right to implement green computing SMK XYZ even need the addition that the original purpose will be achieved. Keywords: green computing, SWOT, ITC